Maximum impact for minimum subsidy: reverse auctions for universal access in Chile and India. Issue 5 (19th August 2014) - Wu, Irene; Blackman, Colin; Blackman, Colin
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose In a minimum subsidy auction (also known as a reverse auction), the government starts by offering the maximum funds available for a given public project; the company requiring smallest subsidy wins. This article discusses how such auctions have been implemented in Chile and India for Internet and mobile phone infrastructure; and identifies lessons for governments considering reverse auctions as a tool. Design/methodology/approach The article investigates several case studies of subsidy auctions in both Chile and India. Findings When firms compete for subsidies in a reverse auctions, they have incentives to get the most result for the least funds. This furthers the government's goal to achieve maximum public policy impact with minimum budget. Originality/value For developing countries, very little research has been done on implementation of auctions in the communications sector.